Generalized Weyl's theorem and tensor product - Rashid, M. H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We give necessary and/or sufficient conditions ensuring the passage of generalized a-Weyl theorem and property $(gw)$ from $A$ and $B$ to $A \otimes B$.